Efficacy and safety of transarterial chemoembolization with CalliSpheres® Microspheres in head and neck cancer - Gao, Fei; Gao, Jinqi; Wang, Kuiyang; Song, Lei (Frontiers in Surgery, 2022)
Objective: Transarterial chemoembolization with CalliSpheres® Microspheres (CSM-TACE) presents favorable efficacy and tolerable safety in several cancers, while its application in head and neck cancer (HNC) is unclear. Thus, the current pilot study aimed to evaluate the efficacy and safety of CSM-TACE in treating HNC. Methods: A total of 15 HNC patients receiving CSM-TACE at the Second Affiliated Hospital of Dalian Medical University from March 2017 to December 2021 were enrolled. Moreover, treatment information, treatment response, progression-free survival (PFS), overall survival (OS), change of liver and renal function indexes, adverse events were recorded. Results: There were 9 patients receiving CSM-TACE as first line and 6 patients receiving CSM-TACE as second or above line treatment; meanwhile, there were 7, 7 and 1 patients undergoing 1 time, 2 times and 3 times of CSM-TACE, respectively. Furthermore, objective response rate (ORR) and disease-control rate (DCR) were 60.0% and 100%, respectively at 1st month; meanwhile, ORR and DCR were 53.3% and 73.3%, accordingly at 2nd month. Moreover, 1-year PFS rate was 34.1%; besides, 1-year OS rate was 38.9%. Additionally, no change of liver function indexes (including TP, ALB, TBIL, ALT and AST) or renal function indexes (including Cr and BUN) was found before and one month after treatment (all P>0.05). Meanwhile, no severe adverse event was found during and after CSM-TACE. Conclusion: CSM-TACE illustrates favorable treatment response and survival benefit, as well as tolerable safety profile in HNC patients.